Reversible conformational changes and fusion activity of rabies virus glycoprotein. - Gaudin, Y (1991)
In an attempt to understand the implication of the rabies virus glycoprotein (G) in the first steps of the viral cycle, we studied the pH dependence of virus-induced fusion and hemagglutination, as well as modifications of the structure and properties of the viral glycoprotein following pH acidification. Our results suggest that the G protein adopts at least three distinct configurations, each associated with different properties. At neutral pH, G did not fuse membranes or hemagglutinate erythrocytes. It was insensitive to digestion with bromelain and trypsin. At pH 6.4, the glycoprotein became sensitive to proteases. Hemagglutination was at its maximum and then sharply decreased with the pH. No fusion was detected. Aggregation of virus was also observed. The third configuration, at below pH 6.1, was associated with the appearance of fusion. Some neutralizing monoclonal antibodies were able to differentiate these three configurations. Preincubation of the virus at below pH 6 inhibited fusion, but this inhibition, like the structural modifications of the glycoprotein, was reversible when G was reincubated at neutral pH.